Single large-scale mitochondrial DNA deletion syndromes: scientific and family conference optimizes the collection of rare disease research outcomes - Laura E. MacMullen; Elizabeth Reynolds; Marissa Weis; Ibrahim George-Sankoh; Sara Nguyen; Katelynn D. Stanley; Mariya Redko; Maria Poblete; Amy C. Goldstein; Rebecca D. Ganetzky (Orphanet Journal of Rare Diseases)
Abstract Background The SLSMDS Research Network is a collaborative network comprising patient advocates, researchers, clinicians, and affected families seeking to improve outcomes for individuals with single large-scale mitochondrial DNA deletion syndromes (SLSMDS). Building off of jointly developed research infrastructures, including a patient registry and natural history study, advocates and clinicians cohosted the SLSMDS Family and Scientific Conference, enabling the collection of patient data from an ultra-rare and geographically dispersed patient population. Here we describe the data collection procedures for single-time point laboratory assessments and patient reported outcomes for a subset of individuals with SLSMDS. Results Utilizing a reproducible model of rare disease data collection, we expand our understanding of the common psychiatric manifestations, describe variability in terms of self-care and quality of life, and emphasize potential biomarkers for individuals with SLSMDS. Conclusion Our study describes how efficient patient-researcher partnerships can develop and sustain novel mechanisms to collect rare disease data, improve our understanding of the natural history of these disorders, and support development of future treatments.